Regulation of the immunomodulatory cytokine IL-10 by Twist2 - Van den Bosch, Mirjam W. M. (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2014)
Dysregulation of cytokines can lead to infectious and inflammatory diseases. The anti-inflammatory cytokine IL-10 is known to control pro-inflammatory cytokines such as TNF-a, IL-6 and IL-12. The regulation of IL-10 is complex and it has been shown previously that the human tumour suppressor PDCD4 is a negative regulator of IL-10 production. Following LPS stimulation, PDCD4 acts as a molecular switch whereby its degradation results in increased IL-10 production. In this study, I have examined in detail the regulation of PDCD4 in LPS- treated macrophages. I have shown that the mTOR pathway and proteosomal degradation are involved in LPS- induced PDCD4 degradation using rapamycin, an mTOR inhibitor, or the proteosomal inhibitors MG132, both of which block this response. Inhibition of PDCD4 degradation by rapamycin also decreased IL-10 and c-Maf expression, a transcription factor critical for IL-10 induction. I have alson found evidence through immunoprecipitation, of interaction between PDCD4 and Twist2. Through chromatin imunoprecipitation (ChIP) and oligonucleotide pull down assays, I have demonstrated a new regulatory role for PDCD4 and Twist2 in LPS-induced IL10 production by showing increased binding of Twist2 to the c-Maf promoter. The PDCD4-Twist2 complex is inhibitory for LPS-induced c-Maf and IL-10 expression. A new mechanism in the complex regulation of the anti-inflammatory cytokine IL-10 has therefore been discovered.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin